Factors contributing to the consumer acceptance of BR smart toward ASLAH Financial-I provided by Bank Rakyat / Noor Azam Mohd Noor - Mohd Noor, Noor Azam (Faculty of Business and Management, 2010)
The purpose of this research is to study the consumer acceptance toward the sales personal skill of BR smart of Bank Rakyat in term of demographic, prospecting and adaptive selling. Moreover, this study will identify the consumer acceptance of BR smart toward ASLAH Financial-I provided by Bank Rakyat as well as their relationship. Therefore, the objective of this research is first to analyse the relationship between prospecting and consumer acceptance. Second is to analyse the relationship between adaptive selling and consumer acceptance. Lastly is to analyse the relationship between demographic and consumer acceptance, in this study, we used interview and questionnaire to identify the relevant aspect regarding the study on the consumer acceptance toward ASLAH Financial-I by BR smart and the other secondary sources such as report, database and so on for data collection. Based on frequency, cross tabulation and contingency coefficient test, a clear finding and result are observed. The findings showed the most customer were agree the consumer acceptance is important to attract the customer to buy the product. The research is also able to give some recommendation and suggestions on how to improve and increase the consumer acceptance after the analysis, finding and interpretation were made.